Penerapan Standar Pelayanan Publik di Kantor Kelurahan Motoboi Kecil Kecamatan Kotamobagu Selatan - Djufri, Diva Natasya; Mozin, Sri Yulianty; Kamuli, Sukarman (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the implementation of public service standards at the Motoboi Kecil Sub-District Office, South Kotamobagu District. The research uses a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation with key informants consisting of local government officials and community members. Data analysis techniques included data reduction, data presentation, and conclusion drawing, while data validity was ensured using the triangulation method. The results indicate that the implementation of public service standards at the Motoboi Kecil Sub-District Office has not been fully optimal. Several obstacles were identified, including a lack of dissemination of service procedures, inefficient service times, additional costs for certain services, limited innovation in digital service delivery, and inadequate facilities, infrastructure, and staffing. Nevertheless, the office has made efforts to implement Standard Operating Procedures (SOPs) for administrative services and provide service information through banners and information officers. This study recommends increasing public outreach, optimizing human resources, and developing technology-based service systems to improve the quality of public services at the Motoboi Kecil Sub-District Offices.